FOLKLOR DAN DIMENSI KISAH KI AGENG DONOLOYO TRADISI UMBUL DONGO DI PUNDEN DONOLOYO DALAM PERSEPSI MASYARAKAT PEMILIKNYA: KAJIAN RESEPSI SASTRA - Ermira Nilansari Putri; Sri Sumarni (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
Judging from the variety of provinces in Indonesia, they also have an influence on the diversity of folklore. This is possible, because basically folklore contains meaning as a culture that is protected by its essence. This study aims to examine the folklore and dimensions contained in the story of Ki Ageng Donoloyo and the umbul dongo tradition. The place of this research was carried out in the Donoloyo Forest Nature Reserve and doubles as Punden Donoloyo. Its address is Watusomo, Watusomo Hamlet, Slogohimo District, Wonogiri Regency, Central Java Province. Primary data sources, from in-depth interviews (punden Donoloyo caretaker, village head, administrators of the Donoloyo Teak Forest Reserve, residents, teachers) and observations or observations in the Donoloyo forest nature reserve (regarding punden and the Donoloyo forest environment). The data analysis technique in this folklore study, the author uses an interactive analysis model. The results of this study contain five dimensions that arise from the existence of this folklore (the dimensions of belief or religion, culture, social, morals, and education). In essence, the reader is faced with a role in terms of providing a meaning or description through (containing space, time and socio-cultural groups). The explanation in the statement can be interpreted that a literary work can be seen from a different point of view (reviewed through reading, evaluation evaluation) by certain people. Keywords: dimensions, folklore, tradition, umbul dongo.